CircMYO9A inhibits influenza A virus replication by dampening haemagglutinin cleavage via increasing SERPINE1/PAI-1 expression - Yiqing Zheng; Xiaoting Zhang; Zhiyuan Liu; Menglu Fan; Lulu Deng; Jihui Ping (Emerging Microbes and Infections)
Circular RNAs (circRNAs) represent a class of widespread and diverse covalently closed circular endogenous RNAs that play critical roles in regulating gene expression in mammals. However, the roles and regulatory mechanisms of circRNAs during influenza A virus (IAV) infection remain largely unexplored. In this study, we screened the circRNA transcription profiles of WSN-infected cells to identify circRNAs involved in viral replication and identified a novel differentially expressed circular RNA, circMYO9A. Mechanistically, circMYO9A acts as a competing endogenous RNA (ceRNA) for SERPINE1/PAI-1 by sponging miR-6059-3p, thereby increasing SERPINE1/PAI-1 expression, which restricts IAV haemagglutinin cleavage and subsequently reduces the infectivity of progeny viruses. Importantly, our findings demonstrate that circMYO9A significantly inhibits viral replication in the lungs of infected mice, potentially increasing their survival during IAV infection. These results demonstrate that circRNAs play crucial roles in inhibiting IAV replication and provide novel insights into potential therapeutic strategies involving circRNAs.